Novel measurements characterizing a ferrite in deep saturation - Kaiser, Jeremias; Bammes, Andreas; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
This paper presents measurements of a ferrite material at very high magnetic field strengths. A N87 toroidal core probe is excited up to deep saturation to get its B-H curve and differential permeability. The test setup contains an air-core coil to get a low-noise derivative of the current by measuring its voltage drop. An audio amplifier supplies the excitation current and an audio interface is used to measure the voltages. The paper describes the processing of the recorded signals and the problems occurring due to the core’s tolerances. A magnetic field strength in the material up to 8000 A/m was reached.
CRIS-Team Scopus Importer:2021-11-05